الشبهات الفقهية والأصولية في قتل وتفجير النفوس المعصومة والرد عليها - مصطفى، عماد إبراهيم خليل (جامعة القصيم, 2017)
الحمد لله رب العالمين والصلاة والسلام على نبيه محمد الأمين صلى الله عليه وعلى آله وسلم تسليماً كثيرا فإن هذا البحث بعنوان الشبهات الفقهية والأصولية في قتل وتفجير المعصومة والرد عليها، لما لهذا الأمر من أهمية خاصة في الواقع وفيه خطورة استباحة الدماء المعصومة في شريعتنا الغراء، والتي رسخت مكانة معروفة وحرمة مؤكدة للحفاظ على حياه معصومي الدم وعدم الاعتداء عليهم. وقد اختار الباحث أن يعرض لأهم الشبهات الفقهية والأصولية في قتل وتفجير النفوس المعصومة والرد عليها من خلال المصادر الشرعية المعتمدة عند أهل السنة والجماعة، ومنهج الوسطية والاعتدال الذي سارت عليه الأمة الإسلامية من عهد نبينا محمد صلى الله عليه وسلم إلى قيام الساعة الذي يجتمع عليه المسلمون في بلاد المسلمين جميعاً؛ لإظهار عظمة هذا الدين وبيان زيف الغالين وتطرف المتطرفين، وتوعية الشباب المسلم من الانحراف مع أفكارهم الهدامة التي جرت ويلات على كثير من البلاد والعباد. ثم ذكر الباحث أسباب قتل وتفجير النفوس المعصومة من قبل هذه الفئة الضالة، وبين حكم عملهم وكيف نتعامل معهم، ثم ختم الباحث بحثه بتوصيات محددة في نفس موضوع البحث وأثبت المراجع التي رجع إليها. Praise be to Allah, prayer and peace be upon the Prophet Muhammad Secretary may Allah bless him and his family peace and recognition of a lot, this research titled suspicions jurisprudence fundamentalism in the bombing and killing of souls infallible and respond to them, because of its particular importance to the seriousness of the violation blood infallible in our religion glue, which cemented the status of well-known and proven to maintain the sanctity of the lives of innocent blood when ordinary Muslims as well as scholars. The researcher chose to introduce the most important suspicions doctrinal fundamentalism in the bombing and killing of souls infallible and respond to them through legitimate sources approved when the Sunnis and the community, and the methodology of moderation, which goes by the Islamic nation from the era of Prophet Muhammad, peace be upon him to do time, which meets the Muslims in Muslim countries are all, to show the greatness of this debt and the falsity of the statement Algalin extremism and extremists and educate young Muslims from deviation with subversive ideas that were the scourge of many of the country and the people. Then he mentioned the reasons for the killing of the researcher and the bombing of souls infallible by this deviant group and the rule of their work and how to deal with them, and then seal the researcher discussed specific recommendations on the same subject of research and proven references that went back to him.
Keywords: الفقه الإسلامي -- الأحكام الفقهية -- شبهات القتل -- قتل النفوس المعصومة